THE IMPLEMENTATION OF RESTORATIVE JUSTICE AT THE WOMEN AND CHILDREN PROTECTION UNIT OF BENGKULU POLICE RESORT (CASE STUDY ON SEXUAL CRIME) - Aziza Yuli Susanti; Antory Royan Adyan; Lidia Br Karo (Universitas Bengkulu, 2020)
The frequent occurrence of cases of which the solutions did not prioritize the best interest for all parties which commonly called as Win-Win Solution resulted in Criminal Justice System to implement Restorative Justice System Justice in which considered to be better because it fix the relation between the victim and the perpetrator. This thesis research used empirical legal research method, the data used was primary, secondary, and tertiary data. The population in this study was all the investigators and co-investigators of Women and Children Protection Unit as well as all the parties who have dealt with Women and Children Protection Unit of Bengkulu Police Resort. Data analysis performed through descriptive qualitative method which elaborates the data in the form of sentences systematically based on the statements obtained from the result of the study in the field. The result of this study was in order to manifest an ideal role, investigators need to undergo development and improvement in various aspects, among others are: it is necessary to do socialization and coordination, improvement of quality as well quantity of adequate human resources, in order to be skillful, tenacious, and responsible and professional.